1983
DOI: 10.1037/0096-1523.9.1.126
|View full text |Cite
|
Sign up to set email alerts
|

Are there limits to binaural additivity of loudness?

Abstract: In recent years there has been notable interest in additive models of sensory integration. Binaural additivity has emerged as a main hypothesis in the loudness-scaling literature and has recently been asserted by authors using an axiomatic approach to psychophysics. Restrictions of the range of stimuli used in the majority of former experiments, and inherent weaknesses of the axiomatic study by Levelt, Riemersma, and Bunt (1972) are discussed as providing reasons for the present investigation. A limited binaur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
2

Year Published

1990
1990
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 22 publications
3
35
2
Order By: Relevance
“…Therefore, in our empirical evaluation of the theory in loudness and brightness, we studied that property. However, although we found substantial support for the it, we observed certain problems in its empirical realization, as had some previous researchers before us (Gigerenzer & Strube, 1983). We concluded the trouble stemmed from unequal number of compound estimate involved in the estimated signals subjected to statistical evaluation (a major culprit is the phenomenon of NEM reported in item 5).…”
Section: Conjoint Commutativitysupporting
confidence: 47%
“…Therefore, in our empirical evaluation of the theory in loudness and brightness, we studied that property. However, although we found substantial support for the it, we observed certain problems in its empirical realization, as had some previous researchers before us (Gigerenzer & Strube, 1983). We concluded the trouble stemmed from unequal number of compound estimate involved in the estimated signals subjected to statistical evaluation (a major culprit is the phenomenon of NEM reported in item 5).…”
Section: Conjoint Commutativitysupporting
confidence: 47%
“…Also studied in psychophysics is how intensity summates when, for example, signals are administered independently to the two ears (Falmagne, 1976;Falmagne, Iverson, & Marcovici, 1979;Gigerenzer & Strube, 1983;Levelt et al, 1972;Schneider, 1988;Steingrimsson & Luce, 2005a, 2005b or the two eyes (Bolanowski, 1987;Bourassa & Rule, 1994;Cohn & Lasley, 1976;Curtis & Rule, 1978;de Silva & Bartley, 1930;de Weert & Levelt, 1974;Ding & Sperling, 2006;Engel, 1969;Grossberg & Kelly, 1999;Irtel, 1998;Levelt, 1965;J. C. Stevens, 1967) and how the two modalities compare (Lehky, 1983;Wade & Ono, 2005).…”
Section: Appendix B Historical Contextmentioning
confidence: 99%
“…Several studies (Algom & Marks, 1984;Levelt, Riemersma, & Bunt, 1972;Marks, 1978Marks, , 1979aMarks, , 1980 have shown that the judgments ofsubjects are, for the most part, consistent with this additive model (but see Gigerenzer & Strube, 1983). These studies also show that both leftand right-ear loudness is a power function of sound intensity; that is, LL(P) = kLPnL and LR(P) = kRpn R , (3) where kL,kR,nL' andnR are constants.…”
Section: Binaural Loudnessmentioning
confidence: 88%